The Effect of Gamified Physical Activities on the Quality of Students' Leisure Time (Case Study: Female Secondary School Students in Ardabil City) - aylar sefidgar; Hamed Kheirollahi Meidani; Mehrdad Moharramzadeh (گردشگری و اوقات فراغت)
Today, with the increasing development of technology and the rise in psychological and physical needs among young people, attention to improving their quality of life has become one of the social priorities. Based on this, the current research was conducted to investigate the impact of physical activities integrated with gamification on students' leisure time quality. This research was applied in terms of its purpose and carried out through a semi-experimental method using the leisure time questionnaire of Ebrahimi et al. (2016). The statistical population included female high school sophomores in Ardabil city, from which 30 were selected by convenience sampling and divided into two groups of 15, experimental and control. Data analysis was performed using Shapiro-Wilk parametric tests, two-way analysis of variance, and Bonferroni's post hoc tests at a significance level of P<0.05 using SPSS 26 software. Investigations showed that time and group factors, along with the interaction between time and group, had significant effects on decision-making skills, leisure awareness, social relations, and self-awareness. These effects were statistically significant in all components with significant levels of P<0.001 and variable effect sizes (d=0.935, d=0.898, d=0.934, and d=0.937 for decision-making skills, leisure awareness, social relations, and self-awareness, respectively). These findings underscore the importance of time and differences between groups in the development and improvement of these skills and emphasize that the interaction between time and group also plays a role in this advancement. According to the results obtained from the research, it can be concluded that the integration of sports exercises with gamification significantly increases the quality of students' free time.